Wage work for women: the menstrual cycle and the power of water - Yasheng Maimaiti; William Stanley Siebert (Institute for the Study of Labor (IZA), 2010)
We hypothesise that women's participation in wage (off-farm) work is reduced when their greater water needs due to the menstrual cycle are not met because their household has poor access to water. For testing, we use the data from rural villages in China. Controlling for village fixed effects, poor access to water is found to decrease the probability of wage work participation of affected (pre-menopause) women by about 10 percentage points, a large effect. As expected, there is no adverse causal impact of poor household access to water for women post-menopause, or for men, ceteris paribus.
Keywords: J16; J21; O15; 330; Wage work; women; menopause; water engineering; rural development; China; Frauenerwerbstätigkeit; Nebentätigkeit; Arbeitszeit; Gesundheit; Dorfwirtschaft; China